Pelaksanaan Pengenalan Lapangan Persekolahan (PLP) FKIP Universitas Mataram Bidang Studi Pendidikan Fisika di MAN 1 Lombok Timur - Randi Kurnia Hidayat; Muhammad Makhrus; Muhammad Iman Darmawan (Prodi Fisika FKIP Unram, 2021)
Universita Mataram conducts Introduction to School Field aims to allow students of undergraduate education programs to gain factual and contextual educational experience in applying a set of knowledge, attitudes and skills that can support the achievement of professional competency mastery, pedagogic, personality, and social as a whole, which boils down to the formation of prospective teachers or educators who are professional and characterful, and able to apply it in the implementation of education and teaching, both in school and outside the school responsibly